2015
DOI: 10.1140/epje/i2015-15118-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEO molecular weight on the miscibility and dynamics in epoxy/PEO blends

Abstract: In this work, the effect of poly(ethylene oxide) (PEO) molecular weight in blends of epoxy (ER) and PEO on the miscibility, inter-chain weak interactions and local dynamics were systematically investigated by multi-frequency temperature modulation DSC and solid-state NMR techniques. We found that the molecular weight (M(w)) of PEO was a crucial factor in controlling the miscibility, chain dynamics and hydrogen bonding interactions between PEO and ER. A critical PEO molecular weight (M(crit)) around 4.5k was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…It has always been a challenging and tempting goal to fabricate high performance polymer materials with a good balance of modulus, elongation, and breaking strength, and thus render the materials to be stiff while at the same time being tough. Therefore, polymer blend has become a pretty straightforward approach to address the above challenges, since it could combine both the merits of two different bulk materials. However, simply blending usually does not work, as the achievement of superior mechanical properties is strongly related with specific polymer conformations, hierarchical structures, and the miscibility between different components, which generally relies on the intermolecular interactions, such as hydrogen bonds, van der Waals interactions, electrostatic interactions, and so on. Herein, elucidating the polymer conformations and intermolecular interactions will provide significant insights into the microscopic origin of the enhanced mechanical properties of polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…It has always been a challenging and tempting goal to fabricate high performance polymer materials with a good balance of modulus, elongation, and breaking strength, and thus render the materials to be stiff while at the same time being tough. Therefore, polymer blend has become a pretty straightforward approach to address the above challenges, since it could combine both the merits of two different bulk materials. However, simply blending usually does not work, as the achievement of superior mechanical properties is strongly related with specific polymer conformations, hierarchical structures, and the miscibility between different components, which generally relies on the intermolecular interactions, such as hydrogen bonds, van der Waals interactions, electrostatic interactions, and so on. Herein, elucidating the polymer conformations and intermolecular interactions will provide significant insights into the microscopic origin of the enhanced mechanical properties of polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…mechanical and rheological) can be optimized. [66][67][68][69] In this study, we further demonstrated the robust performance of the proposed pulse sequences on polymer blend PMMA/PB; their chemical structures are shown in Figure 1. PMMA is a semi-crystalline polymer with glass transition (Tg) and melting (Tm) temperatures both above 100 o C, whereas PB is a viscous liquid with a Tg of ~ -90 o C. Therefore, in the PMMA/PB blend, PMMA is considered as the rigid and PB is the mobile components.…”
Section: Resultsmentioning
confidence: 60%
“…For preparing the PHBH/PCL blend by solution casting, PCL of M n 10 kDa was preferred because low-molecular-weight polymers have higher chances of interacting with other polymers. , The photograph of the resulting unheated PHBH/PCL blend film (Supplementary Figure S7) showed a spiderweb-like pattern, indicating the heterogeneous, macroscale phase separation of the two polymers. This suggests that the two polymers are not completely miscible, although the blend film appears macroscopically smooth and homogeneous after heat pressing (data not shown).…”
Section: Resultsmentioning
confidence: 99%